Long-term oncological outcomes after laparoscopic radical prostatectomy - Fiedler, Marcel; Lorenzo Bermejo, Justo; Flinspach, Bettina; Schulze, Michael; Teber, Dogu; Rumpelt, Hans Joachim; Rassweiler, Jens Jochen (BJU international, 2013)
What's known on the subject? and What does the study add? Laparoscopic radical prostatectomy (LRP) has shown good oncological short-term and mid-term outcomes, but long-term outcomes are still lacking. We present long-term oncological outcomes of LRP in a large cohort of patients operated on in one of the pioneering European centres. The data from the present study show high rates of biochemical and clinical recurrence-free survival and low cancer-specific mortality compared with open series. Objectives To investigate long-term oncological outcomes after laparoscopic radical prostatectomy (LRP). To identify parameters influencing recurrence-free survival in a single-institution series. Patients and Methods All patients underwent LRP using the transperitoneal retrograde Heilbronn technique. High-risk patients received adjuvant treatment according to an institutional algorithm based on prostate-specific antigen (PSA), Gleason score, tumour-node-metastasis stage, margin status and tumour volume. Data were collected prospectively on operative and postoperative parameters beginning in 1999. Complete follow-up data of 370 of the first 500 consecutive patients are available. Biochemical recurrence was defined as two consecutive PSA levels <0.2 ng/mL within the follow-up period. Kaplan-Meier estimates and Cox regression were applied to examine recurrence-free survival times. Results The estimated biochemical recurrence-free survival (BCRFS) rates 10 years after LRP were 80.2% in patients staged pT2, 47.4% in those staged pT3a and 49.8% in those staged pT3b/4, confirming a better prognosis in patients with organ-confined disease (P < 0.001). In the multivariate Cox regression analysis, only Gleason score and pT stage significantly influenced BCRFS. The 10-year clinical progression-free survival rates were 97.2% (pT2), 84.4% (pT3a) and 78.1% (pT3b/4), and prostate cancer-specific survival estimates were 100% (pT2), 97.3% (pT3a) and 90.6% (pT3b/4). Conclusions The 10-year biochemical and clinical progression-free survival after LRP combined with a risk-adapted concept of adjuvant therapy is high, while prostate-cancer specific mortality is low. Our data shows no negative impact of laparoscopic techniques on oncologic outcomes compared to large series after retropubic radical prostatectomy. In a multivariate Cox regression, only Gleason score and pT stage had significant impact on BCRFS.
Gesehen am 29.10.2021